Statistical analysis plan for the ‘Rapid Intervention with Glyceryl trinitrate in Hypertensive stroke Trial-2 (RIGHT-2)’ - Scutt, Polly; Appleton, Jason P.; Dixon, Mark; Woodhouse, Lisa J.; Sprigg, Nikola; Wardlaw, Joanna M.; Montgomery, Alan A.; Pocock, Stuart J.; Bath, Philip M.W. (SAGE, 2018)
Rationale: Glyceryl trinitrate, a nitric oxide donor, is a candidate treatment for acute stroke; it lowers blood pressure, does not alter cerebral blood flow or platelet function and is neuroprotective in experimental stroke. The ongoing rapid intervention with glyceryl trinitrate in hypertensive stroke trial-2 trial aims to assess the safety and efficacy of paramedic-delivered glyceryl trinitrate in patients with ultra-acute stroke.